Change in the Frequency of Diabetic Ketoacidosis in Children with Newly Diagnosed Type 1 Diabetes in the Central Anatolia Region of Turkey over the Years Before and After the Coronavirus Disease 2019 Pandemic: A Single-Center Experience - Serkan Bilge Koca; Mehmet Zahit Takcı; Recep Deniz; Serhan Özcan; Mehmet Çeleğen; Adem Dursun (AVES Yayincilik, 2024)
Objective: The number of admissions for severe diabetic ketoacidosis (DKA) in children with newly diagnosed type 1 diabetes (T1D) increased during the coronavirus disease 2019 pandemic. We aimed to investigate whether there has been a change in this situation in recent years. Materials and Methods: All children with T1D who were diagnosed in our tertiary hospital between 2019 and 2023 were included. Plasma insulin, C-peptide, hemoglobin A1c (HbA1c), and antibodies against thyroid peroxidase, thyroglobulin, insulin, islet cell, glutamic acid decarboxylase, tissue transglutaminase IgA, and endomysium IgA were measured. Results: The frequency of moderate-severe acidosis at admission, which increased after pandemic period compared to the pre-pandemic period, returns to its previous levels over time but still shows a statistical difference compared to the pre-pandemic period (P = .012). Age, blood gas pH and HCO3 level, C-peptide, HbA1c, and length of stay of children at the time of admission were compared year by year (years 2019-2023). No statistical differences were observed (P = .509, P = .181, P = .069, P = .469, P = .346, P = .946), respectively. A significant difference was observed in venous glucose (P < .001) and insulin (P = .001) according to years. Also, no significant difference was found about the degree of acidosis according to age (P = .334). Conclusion: Although the frequency of DKA in children with newly-diagnosed T1D increased in the first years of the pandemic, it has been decreasing over the years toward pre-pandemic levels. The frequency of DKA is still higher than the pre-pandemic period.